THE IMPROVING EMPLOYEE PERFORMANCE IN LARGE-SCALE OF MANUFACTURING-INDUSTRIAL WORKERS THROUGH THE ORGANIZATION'S CLIMATE REINFORCEMENT, THE TRAINING, CAREER SUCCESS AND WORK MOTIVATION IN PALEMBANG - Susi Handayani; Musa Hubeis; Nancy Yusnita (Yayasan Education and Social Center, 2023)
This research aims to investigate employee performance improvement strategies in large-scale manufacturing industries in Palembang by integrating organizational climate strengthening, training, career success, and work motivation. Specifically, this investigation will focus on the manufacturing industry in Palembang. The mixed method is used, which provides a comprehensive understanding of the factors that contribute to improving employee performance by combining quantitative and qualitative approaches. The findings from this study indicate that Organizational Climate has a significant positive impact on employee motivation (t-statistic value = 2.639, P-Value = 0.004). Improving Organizational Climate has the potential to increase Work Motivation. In addition, Organizational Climate also has a significant positive effect on Employee Performance (t-statistic value = 1.966, P-Value = 0.025). Improving Employee Performance can also be achieved through this factor. Training positively and significantly impacts employee motivation (t-statistic value = 3.257, P-value = 0.001). Improvements in training also have a positive and significant impact on Employee Performance (t-statistic value = 2.264, P-Value = 0.012). Employee success also significantly affects employee motivation (t-statistic value = 3.341, P-value = 0.000). Career development can increase Work Motivation, and an increase in Career Success also contributes positively and significantly to Employee Performance (t-statistic value = 2.243, P-Value = 0.013). Work Motivation wholly and substantially influences Employee Performance (t-statistic value = 2.314, P-value = 0.011). These findings confirm that higher work motivation can help improve employee performance. The P-value = 0.013). Work Motivation positively and significantly affects Employee Performance (t-statistic value = 2.314, P-value = 0.011). This finding confirms that higher work motivation can help improve employee performance. The P-value = 0.013). Work Motivation positively and significantly influences Employee Performance (t-statistic value = 2.314, P-value = 0.011). These findings confirm that higher work motivation can help improve employee performance. The role of work motivation mediators is investigated, and this research reveals several significant findings related to that role. There is no significant influence between organizational climate and employee performance through work motivation as a mediator (the significance level of the P-value for the Sobel test is 0.065). Despite this, training has been shown to significantly impact employee performance, with work motivation serving as a mediator (significance P-value from the Sobel test = 0.036). Career success has a significant indirect effect on employee performance, mediated by work motivation (the considerable p-value for the Sobel test is 0.035).